Impacto da capacidade funcional e síndrome de fragilidade na mortalidade de idosos internados em Unidade de Terapia Intensiva: estudo prospectivo - Ricci, Tainá Gabriela [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Introduction: In Brazil we have 32.3 million elderly people in 2022, corresponding to 15.1% of the population. Aging promotes loss of physiological reserves and an increase in diseases, which can lead to loss of functional capacity and frailty syndrome. These conditions need to be assessed in hospitalized elderly people, as dependent and frail individuals may have worse outcomes. Objectives: To evaluate the association between the degree of severity, frailty and functional capacity of elderly people admitted to the Intensive Care Unit of the HCFMB and the outcomes presented after 180 days of hospital discharge. Materials and methods: It is a prospective observational study, carried out at HCFMB. Elderly patients admitted to the Intensive Care Units (ICU) of the HCFMB were included, and sociodemographic and clinical assessments, SOFA severity score, functionality by the Katz Index and frailty by the FRAIL Index were performed. Follow-up was carried out during the entire stay in the ICU and in the HCFMB, after 30 days and 180 days after hospital discharge, evaluating the outcomes (length of stay, post-discharge readmission and mortality) and reassessing functionality and frailty. Results: From January to November 2021, 153 elderly people with a mean age of 70.6 (± 7.2) years were evaluated. The number of diseases reported before hospitalization averaged 3.4 (± 1.9), the most prevalent being SAH (70.6%). The length of hospital stay was 19.0 (± 14.2) days, and for ICU stay 14.5 (± 12.6) days. 53.6% of individuals died in the hospital environment. In the period of 30 days after discharge, the total number of deaths was 54.2% and after 180 days, the total number of deaths was 60.1%. The SOFA had an average of 6.8 (± 5.0) points. 76.3% of participants had a score equal to or greater than 2. Dependent patients (score <4) totaled 8.5%. After 30 days, 22.7% were dependent and at 180 days, 18.7%. On admission, robust patients represented 26.1%, at 30 days 13.8% and 180 days 27.1%. Patients with SOFA >2 had longer ICU and hospital stays. In the association of functional capacity and frailty, an association was observed. An association was observed between SOFA score >2 and death within 180 days. In the bivariate analyses, an association was observed between SOFA >2, hospitalization for medical reasons and hospitalization for COVID-19 with mortality (p<0.05). In the multivariate analyses, SOFA > 2, hospitalization for medical reasons, hospitalization for COVID 19, and length of stay in the ICU and hospital were associated with the death event. Conclusion: A SOFA score > 2, reason for clinical and COVID-19 hospitalization, length of hospital and ICU stay were associated with mortality in this study.

Introdução: No Brasil temos 32,3 milhões de idosos em 2022, correspondendo à 15,1% da população. O envelhecimento promove perda nas reservas fisiológicas e aumento de doenças, que podem levar à perda da capacidade funcional e síndrome da fragilidade. Essas condições são necessárias de serem avaliados nos idosos internados, pois os indivíduos dependentes e frágeis podem apresentar piores desfechos. Objetivos: Avaliar a associação entre grau de gravidade, fragilidade e capacidade funcional de idosos internados em Unidade de Terapia Intensiva do HCFMB e os desfechos apresentados após 180 dias de alta hospitalar. Materiais e métodos: É um estudo observacional prospectivo, realizado no HCFMB. Foram incluídos pacientes idosos internados nas Unidades de Terapia Intensiva (UTI) do HCFMB e realizada avaliações sociodemográficas e clínicas, do escore de gravidade SOFA, funcionalidade pelo Índice de Katz e fragilidade pelo Índice FRAIL. Foi realizado seguimento durante toda a internação na UTI e no HCFMB, após 30 e 180 dias após a alta hospitalar avaliando os desfechos (tempo de internação, reinternação pós-alta e mortalidade) e reavaliação da funcionalidade e fragilidade. Resultados: No período de janeiro a novembro de 2021 foram avaliados 153 idosos com média de idade de 70,6 (± 7,2) anos. O número de doenças referidas antes da internação teve média de 3,4 (± 1,9), sendo a mais prevalentes HAS (70,6%). O tempo de internação hospitalar foi de 19,0 (± 14,2) dias, e para internação na UTI de 14,5 (± 12,6) dias. 53,6% dos indivíduos evoluíram a óbito no ambiente hospitalar. No período de 30 dias após alta o total de óbito foi de 54,2% e após 180 dias o total de óbito foi de 60,1%. O SOFA teve média de 6,8 (± 5,0) pontos. 76,3% participantes tiveram pontuação igual ou maior que 2. Os pacientes dependentes (pontuação <4) totalizaram 8,5%. Após 30 dias, 22,7% eram dependentes e em 180 dias eram 18,7%. Na internação os pacientes robustos representavam 26,1%, em 30 dias 13,8% e 180 dias 27,1%. Os pacientes que tiveram SOFA >2 apresentaram maior tempo de internação em UTI e hospitalar. Na associação da capacidade funcional e fragilidade, foi observada associação. Foi observada associação com escore SOFA >2 com evento óbito em 180 dias. Nas análises bivariadas foram observadas associação entre o SOFA >2, internação por motivo clínico e internação por COVID-19 com a mortalidade (p<0,05). Nas análises multivariadas, o SOFA > 2, internação por motivo clínico, internação por COVID-19 e o tempo de internação em UTI e hospitalar tiveram associação com o evento óbito. Conclusão: Um escore SOFA > 2, motivo de internação clínica e por COVID-19, o tempo de internação hospitalar e em UTI, foram associados a mortalidade neste estudo.
Impact of functional capacity and frailty syndrome in the mortality of elderly people hospitalized in the Therapy Unit Intensive: prospective study
Keywords: Elderly; Fragility; Functionality; Intensive care unit; Unidades de terapia intensiva; Idosos; Mortalidade; Fragilidade; Pacientes internados